3D MODELING IN EDUCATION - Doniyor Ibadullayev (Bright Mind Publishing, 2025)
This paper collects and analyzes information about 3D models in education. The advantages and disadvantages of using 3D models in different disciplines, fields and directions were discussed. Teaching using 3D objects can be more understandable, interesting and exciting, and the skills to use the classroom effectively are also presented.
Keywords: 3d, model, visualization, VR, education.